Biological Effectiveness of Ion Beam for In Vitro Cell Irradiations - Li, Heng (Frontiers in Oncology, 2022)
Despite numerous ion beam irradiation of cell experiments performed over the past five decades, the relationship between the biological effectiveness of ion beams and the physical characteristics of the ion beam remains unclear. Using 1118 sets of in-vitro cell survival experiments with ion-beam irradiation, complied by the Particle Irradiation Data Ensemble (PIDE) project, the relationship between cell survival and the fluence and linear energy (LET) of the ion beam was established. Unlike previous studies, the closed-form analytical function is independent of photon irradiation and takes a universal form across all ion and cell species. The new under-standing of the biological effectiveness of ion beams is crucial for predicting tumor response and toxicities in ion-beam radiation therapy, along with radiation protection for high LET ion beams with low fluence.